2014
DOI: 10.1021/nn501376z
|View full text |Cite
|
Sign up to set email alerts
|

Charging the Quantum Capacitance of Graphene with a Single Biological Ion Channel

Abstract: The interaction of cell and organelle membranes (lipid bilayers) with nanoelectronics can enable new technologies to sense and measure electrophysiology in qualitatively new ways. To date, a variety of sensing devices have been demonstrated to measure membrane currents through macroscopic numbers of ion channels. However, nanoelectronic based sensing of single ion channel currents has been a challenge. Here, we report graphene-based field-effect transistors combined with supported lipid bilayers as a platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…[147] Nevertheless, most researches on graphene biointerfaces still use graphene on rigid solid substrates at an intermediate stage mainly focusing on understanding the complicated sensing mechanisms (as the reconfiguration of the fluidic-like lipid layer has to be considered). [149,150,151] For example, a gram-negative bacteria biomimetic membrane was deposited on CVD GFETs (fabricated on a SiO 2 /Si substrate) for detecting magainin 2, an antimicrobial agent. The presence of magainin 2 disrupts and thins the lipid membrane from a thickness of ~5 nm to ~3 nm.…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[147] Nevertheless, most researches on graphene biointerfaces still use graphene on rigid solid substrates at an intermediate stage mainly focusing on understanding the complicated sensing mechanisms (as the reconfiguration of the fluidic-like lipid layer has to be considered). [149,150,151] For example, a gram-negative bacteria biomimetic membrane was deposited on CVD GFETs (fabricated on a SiO 2 /Si substrate) for detecting magainin 2, an antimicrobial agent. The presence of magainin 2 disrupts and thins the lipid membrane from a thickness of ~5 nm to ~3 nm.…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
“…[151] Graphene bioelectronics for cellular sensors will be further discussed in the next Section 4.3.…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QC of a single-layer graphene [17] was first measured by Xia et al in an ionic liquid and in an aqueous solution of salt [18]. Some of the more recent studies of the graphene QC in aqueous solutions involve a correlated in situ electrochemical Raman spectroscopy [19], as well as charging of graphene through a biological ion channel in a lipid bilayer adjacent to graphene [20], showing the versatility and the promise of operating graphene devices in the capacitor mode. It is noteworthy that most of the above-mentioned studies of solution-gated graphene devices have achieved quite high doping densities of graphene by both electrons and holes, reaching the range of 10 13 -10 14 cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the conductivity of the 1D channel of an SWNT is sensitive to individual positive ions—attributed to the simultaneous drop in mobility and charge transfer . Surprisingly, although charged entities in liquid phase (electrolytes) are well known for highly efficient gating, the possibility of a vapor‐phase gating by a stream of charged particles has not yet been explored.…”
mentioning
confidence: 99%